Scattering Improves Temporal Resolution of Vision: A Pilot Study on Brain Activity - Francisco J. Ávila (Photonics)
Temporal vision is a vital aspect of human perception, encompassing the ability to detect changes in light and motion over time. Optical scattering, or straylight, influences temporal visual acuity and the critical flicker fusion (CFF) threshold, with potential implications for cognitive visual processing. This study investigates how scattering affects CFF using an Arduino-based psychophysical device and electroencephalogram (EEG) recordings to analyze brain activity during CFF tasks under scattering-induced effects. A cohort of 30 participants was tested under conditions of induced scattering to determine its effect on temporal vision. Findings indicate a significant enhancement in temporal resolution under scattering conditions, suggesting that scattering may modulate the temporal aspects of visual perception, potentially by altering neural activity at the temporal and frontal brain lobes. A compensation mechanism is proposed to explain neural adaptations to scattering based on reduced electrical activity in the visual cortex and increased wave oscillations in the temporal lobe. Finally, the combination of the Arduino-based flicker visual stimulator and EEG revealed the excitatory/inhibitory stimulation capabilities of the high-frequency beta oscillation based on the alternation of an achromatic and a chromatic stimulus displayed in the CFF.